THE EFFECT OF WORKING CAPITAL EFFICIENCY AND THE LEVEL OF LIQUIDITY ON PROFITABILITY IN THE MINING INDUSTRY REGISTERED IN INDONESIA STOCK ECHANGE - Etty Harya Ningsi (Enrichment : Journal of Management, 2021)
Every company aims to seek profitability. To achieve the expected profit, management must be able to take appropriate policies in investing funding sources that are available so that the sufficient liquidity and working capital efficiency will be obtained and ultimately the expected profitability will be obtained as well. The purpose of this study was to determine how much influence the efficiency of working capital and the level of liquidity have on profitability in the mining industry on the Indonesia Stock Exchange. This study took time series data in the form of financial reports for the period 2009 to 2010. The data were analyzed using the classical assumption test, multiple linear regression, and hypothesis testing using the F test and t test. Based on the research results, it is known that there is a significant influence between the efficiency of working capital and the level of liquidity on profitability.